1 - Genocidal Violence in the Making of Nation and State in Ethiopia - Mekuria Bulcha, (African Sociological Review, 2004)
Based on a qualitative historical-sociological investigation of the incidents of mass-killings that have been registered during the last one hundred and fifty years, this study concludes that both the unification of the Abyssinian state between 1850s and 1870s and the creation of the Ethiopian empire state during last quarter of the nineteenth century were accomplished through wars that were clearly genocidal. Though their aims were building a state, there were differences between the types of state and nation envisaged by the two ‘categories’ of rulers. The attempts of the nineteenth century rulers were to purge the Abyssinian state of non-Abyssinian religious and ethnic communities they perceived as ‘alien’ in order to build an exclusive Abyssinian state and a homogenous Abyssinian nation. The nationalism of late nineteenth century rulers, as represented by its architect Menelik II, was expansionist. Abandoning the idea of Abyssinian homogeneity, they opted for hegemony over other peoples they had conquered in the heyday of the European scramble for Africa. The result was a multinational empire state. This study shows that policies used to build and maintain the empire state were implemented using methods that were ethnically oppressive, immensely exploitative, and genocidal. This had triggered ethnic nationalism that has been at logger-heads with the ‘official’ nationalism of the dominant ethnic group. Moreover, the conflict between the two brands of nationalism had increased in tandem with rising ethnic consciousness and intensified since the mid 1970s as a consequence the policies of the Dergue. In order to legitimate the state, control dissent, and stay in power the ruling elites built a huge military apparatus and used retributive genocidal killings. The study confirms that there is clear nexus between authoritarian rule, man-made famines, and genocide in Ethiopia. It suggests that there are several warning signs showing that genocide is in the making today. Taking the international context into account, the study indicates that the role of some Western etting rather than deterring genocide in Ethiopia.